Accelerated institutionalization of an adolescent sexual and reproductive health (ASRH) intervention in Tanzania: Findings from a mixed-methods evaluation - Meghan Cutherell; Juliana Bwire; Edwin Mtei; Abednego Musau; Catherine Kahabuka; Catherine Kahabuka; Isabellah Luhanga; Isabellah Luhanga; Augustino Julius; Gerald Kihwele (Frontiers Media S.A., 2023)
IntroductionFrom 2018 to 2020, Adolescents 360 (A360), aiming to increase demand for and voluntary uptake of modern contraception among adolescent girls 15-19 years, designed and scaled an intervention in Tanzania (Kuwa Mjanja) to 13 regions through project-funded expansion. In 2020, the project began to develop a strategy for its follow-on phase, focusing on program sustainability. In this process, funder priorities led to a decision to exit A360's programming in Tanzania over a 15-month exit period. A360 elected to pursue a process of expedited institutionalization of Kuwa Mjanja into government systems during this period.Materials and methodsThe institutionalization process was facilitated in 17 local government authorities in Tanzania. Quantitative and qualitative data were gathered and analyzed including time-trend analysis of routine performance data, statistical analysis of two rounds of client exit interviews, and thematic analysis of qualitative research.ResultsThe sociodemographic characteristics of adolescent girls reached under government-led implementation were comparable to those reached by A360-led implementation. Intervention productivity decreased under government-led implementation but remained consistent. Adopter method mix shifted slightly toward greater long-acting and reversible contraceptive uptake under a government-led model. Factors that enabled successful institutionalization of Kuwa Mjanja included the presence of youth-supportive policies, the establishment of school clubs which provided sexual and reproductive health education, commitment of government stakeholders, and appreciation of adolescent pregnancy as a problem. Some intervention components were important for program effectiveness but proved difficult to institutionalize, primarily because of resource constraints. Lack of adolescent sexual and reproductive health (ASRH)-focused targets and indicators disincentivized Kuwa Mjanja implementation.DiscussionThere is significant potential in operationalizing user-centered ASRH models within government structures, even in a narrow time frame. A360 saw similar performance under government-led implementation and fidelity to the unique experience that the program was designed to deliver for adolescent girls. However, beginning this process earlier presents greater opportunities, as some aspects of the institutionalization process that are critical to sustained impact, for example, shifting government policy and measurement and mobilizing government resources, require heavy coordination and long-term efforts. Programs pursuing institutionalization in a shorter time frame would benefit from setting realistic expectations. This may include prioritizing a smaller subset of program components that have the greatest impact.